STIs among YMSM in Canada: Implications for Public Health Policies, Programs and Activities - Foley, Simon (Université d'Ottawa | University of Ottawa, 2014)
Men who have sex with men (MSM) experience a disproportionate burden of sexually transmitted infections (STIs) in Canada and the United States. Since the beginning of national HIV surveillance in Canada in 1985, MSM have accounted for more than 54.1 % (n = 22,500) of total positive HIV diagnoses up to 2012, and have been estimated to carry the greatest number of diagnosed and undiagnosed HIV infections (46.7%; n = 33,330).1 In recent years, STIs among younger MSM (known as young men who have sex with men or YMSM) has emerged as a field of research for those with an interest in sexually transmitted infectious diseases. This paper uses YMSM in Canada as a case study, and applies a systematic review approach to provide evidence on current epidemiologic trends relating to STIs among YMSM in Canada, as well as related policy implications. The systematic approach was selected for a variety of reasons; it was selected to report transparently on how the conclusions were generated, to reduce bias in findings, and to draw upon the most relevant (but also hard to find) information. Additionally, systematic reviews, such as Cochrane systematic reviews and meta-analyses, are increasingly the preferred method for conducting literature reviews in the fields of the biomedical and social sciences, and are becoming more prominent in a world that increasingly privileges evidence in decision-making. Using systematic review methods, this paper finds that in Canada, the incidence of reported HIV infections among YMSM has been increasing since 1999 and YMSM are considered to be at risk for a variety of other STIs. It further finds that the burden of some STIs is concentrated among older MSM as opposed to YMSM. Furthermore, there are a variety of proposed public health policies (primary and secondary prevention activities) that might address the burden of HIV infections and STI risk behaviour among YMSM; these include a comprehensive approach to determinants of sexual health; continued sexual health education targeting YMSM; new, novel approaches for reaching YMSM; better capacity to address young men’s health needs; increased STI screening and testing, in particular point of care and rapid testing for HIV; and increased data collection on YMSM. These policy implications would affect all levels of government in Canada (national, provincial, and territorial, and municipal), as well as non-governmental organizations (NGOs).